British Diplomatic Attitudes towards Europe, 1801–4Ignorant and Indifferent?. Issue 4 (7th August 2016) - Goldsmith, Thomas
ABSTRACT: Recent decades have seen a rehabilitation of the reputation of Henry Addington's and Lord Hawkesbury's foreign policy during the course of the former's government, 1801–4. Nevertheless, the existing historiography has done little to place their actions in the wider context of British foreign policy in the early nineteenth century, nor to assess them in light of the debate around the arguments of Paul W. Schroeder's systemic theories and his attacks on eighteenth-century balance-of-power politics. This article argues that Schroeder's theories need qualifying in relation to this period and shall demonstrate that Addington and Hawkesbury conducted a logical, consistent, and Euro-centric balance-of-power policy, and one rooted in rules and assumptions governing their conduct, rather than a pell-mell free-for-all diplomatic system. It furthermore raises questions as to the continuity in British foreign policy and the need for additional research in this area.